43=t/6+40

Simple and best practice solution for 43=t/6+40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43=t/6+40 equation:



43=t/6+40
We move all terms to the left:
43-(t/6+40)=0
We get rid of parentheses
-t/6-40+43=0
We multiply all the terms by the denominator
-t-40*6+43*6=0
We add all the numbers together, and all the variables
-1t+18=0
We move all terms containing t to the left, all other terms to the right
-t=-18
t=-18/-1
t=+18

See similar equations:

| z-3=1/2 | | 5(s+8)=75 | | 2(4-5x)=-68 | | 9m=189 | | 0.5(x+2)=0.5(3x+4) | | h/2-7=25 | | 4x-3(4x-3)=3-3(2x-6) | | w/3+7=11 | | 14x+7=9x+47 | | 4(1–x)-2x=3x–1 | | 15-1v=-3 | | v=1/3(3.14)(6)^2(2) | | 2.7x+3=3.2x+9.6 | | 3p=7p-8/5 | | (2x-5)/5=4 | | v=1/3(3.14)(2)^2(6) | | 4x=64.4 | | 4x-3=6(x+1)-7 | | 4(1-x)-2=3x-1 | | 4y-17=2y+3 | | 8.7h-9.55-13.2h=14.85-2.5h | | 3a−8=4+a | | 5x2+55x=210 | | z-3=1/3 | | 6p−6p=0 | | x2/5+3=1 | | 2=g-82^5 | | -7x65= | | 9x+5x-54x-5=0 | | 100-9(3x+15)-12(4x-9)+34=150+2(x-3)-(4x-7)-34 | | 11+8x=27 | | 4x+43=10x+40 |

Equations solver categories